2002
DOI: 10.1509/jimk.10.3.1.19546
|View full text |Cite
|
Sign up to set email alerts
|

The Perennial Issue of Adaptation or Standardization of International Marketing Communication: Organizational Contingencies and Performance

Abstract: The author investigates the standardization/adaptation issue in international advertising from an organizational perspective, introducing two variables: knowledge of local market conditions at the center (exporter/headquarters level) and headquarters’ influence on local marketing decisions. The author interviewed 150 Norwegian exporters by mail on their experience in this respect. The results reveal that the two dimensions indeed have some impact on how firms develop their international marketing strategies. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 35 publications
(48 reference statements)
5
108
1
3
Order By: Relevance
“…As many firms did not use an independent intermediary in one or more of the markets and some firms did not complete the questionnaire for all four markets, we ended up with information concerning a total of 212 cases of independent intermediaries from 117 case companies. The average sales volume of the total sample was NOK 557 million, which is very in line with the NOK 552 million average obtained by Solberg (2002) in his study of Norwegian exporters based on a randomized sample.…”
Section: Methodssupporting
confidence: 85%
“…As many firms did not use an independent intermediary in one or more of the markets and some firms did not complete the questionnaire for all four markets, we ended up with information concerning a total of 212 cases of independent intermediaries from 117 case companies. The average sales volume of the total sample was NOK 557 million, which is very in line with the NOK 552 million average obtained by Solberg (2002) in his study of Norwegian exporters based on a randomized sample.…”
Section: Methodssupporting
confidence: 85%
“…In the wake of the globalisation trends the last couple of decades a number of writers have examined the content of internationalisation strategy -as opposed to the process -(e.g. Craig/Douglas 2000, Hout et al 1982, Porter/Takeuchi 1986, Jain 1989, Ohmae 1989, Yip 1995, Solberg 1997, Zou/Cavusgil 1996, 2002. Different dimensions of strategy have been treated, for instance: -Standardisation/adaptation of the marketing mix -Coordination and control of operations -Centralisation/decentralisation of decisions -Market concentration/market spread -Consolidation/expansion -Sequencing of market entry -Competitive reaction -Entry/operation modes We have adopted the classification presented by Solberg (1997) and Solberg et al (2004), who identified nine different strategies.…”
Section: Strategy Development Network Access and International Commimentioning
confidence: 99%
“…Although adaptation and autonomy levels are closely related (see, e.g., Krum and Rau 1993;Laroche et al 2001;Solberg 2002), and although our one-item measure of adaptation intentions yielded similar findings, planned autonomy levels do not perfectly reflect such intentions. Thus, our findings should be interpreted with some caution.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 58%
“…Many researchers agree that "the issue of standardization versus differentiation is related directly to that of centralization versus decentralization" (Krum and Rau 1993, p. 51; see also Hamilton and Kashlak 1999;Laroche et al 2001;Solberg 2002). Özsomer and Simonin (2004, p. 402 [emphasis in original]) state that "standardization is achieved through a tight linkage of decision making (centralization) between the subsidiary and the head office.... MNCs that implement standardized marketing programs want to protect and defend their … marketing mix elements by tightly centralizing decision making."…”
Section: Dependent and Main Independent Variablesmentioning
confidence: 99%